Case Report: Nutritional Examination of Weight Loss Treatment Using Kampo - Matsui, Yutaka; Matsui, Ikuko (Frontiers in Nutrition, 2021)
Loss of appetite is a common symptom in patients with dementia, and if weight loss or difficulty eating occurs without subjective symptoms, the patient can easily become malnourished. There is also a close relationship between dementia and physical frailty, such as weight loss and muscle weakness, and thus early intervention to address frailty in patients with dementia is important. In this study, 3 patients with dementia who complained of loss of appetite and weight loss showed increases in body weight and muscle mass after taking Ninjin'yoeito. Ninjin'yoeito was found to be a potentially effective treatment option for physical frailty in patients with dementia.